BiVO4-Driven photocatalytic degradation of pharmaceutical in Slurry Bubble Column Reactor: Influencing factors and toxicological profiling - Obaid Qamar, Mohammad; Balu, Krishnakumar; Ahn, Young-Ho (Chemical engineering journal (Lausanne, Switzerland : 1996), 2024)
[Display omitted] •Synthesized peanut-like BiVO4 photocatalysts via a pH-controlled method.•Explored key factors enhancing photocatalytic efficiency.•Achieved high k = 0.1069 min−1 in SBCR for efficient Tetracycline removal.•Utilized ECOSAR Model for Toxicological Profiling of intermediates. As the pursuit for sustainable and effective solutions to address environmental pollution intensifies, a comprehensive approach in photocatalysis has become a subject of increasing interest. In this study, BiVO4 photocatalyst synthesized through a pH-controlled hydrothermal method was used for the degradation of tetracycline (TET), a prevalent pharmaceutical pollutant. Optimal conditions, particularly a pH of 9 and enriched dissolved oxygen (DO), significantly improve TET removal, achieving a 96 % degradation efficiency with a rate constant of k = 0.1069 min−1. The investigation revealed that the degradation predominantly involves the generation of reactive oxygen species (ROS), notably O2•−, which play a crucial role in the degradation of TET. Using the “ecological structure–activity relationships” (ECOSAR) program, the toxicity of the intermediates was assessed, highlighting the environmental implications of the photocatalytic process. In addressing the scalability for industrial applications, a Slurry Bubble Column Reactor (SBCR) was employed, and separation-stability tests of the photocatalyst were conducted. These tests confirmed the photocatalyst’s long-term effectiveness and stability, underscoring its potential for repeated use in large-scale applications. This comprehensive research not only underscores the potential of BiVO4 in removing environmental contaminants but also provides vital insights into ecological safety.